Effect of water regime on the dynamics of free ammonia during high solid anaerobic digestion of pig manure. (January 2023) - Su, Jian; Lv, Wenjuan; Ren, Liheng; Kong, Xiaoliang; Luo, Lin; Awasthi, Mukesh Kumar; Yan, Binghua
Abstract: Free ammonia (FAN) inhibition is commonly encountered during high solid anaerobic digestion (HSAD) of pig manure. The performance of HSAD is highly related to its operational water regime; however, little information is available regarding the dynamics of free ammonia with varied water regimes. In this work, four treatments were set with equal amount of water supply but varied addition frequencies, i.e. add once but at different times in treatments T1 and T2, add twice in T3 while it was three times in treatment T4. Results showed that the whole methanogenic process ran smoothly with the average methane gas production rate maintaining at 191.1 LCH4 /kgVSadded . Although a higher methane gas production rate of 217.4 LCH4 /kgVSadded was achieved in T1, one time water addition triggered a higher ammonia inhibition potential. Cumulative FAN release was 6.03 mgFAN/kgVSadded in T1 while the balance between FAN and ammonia tended to the fraction of FAN. In T4, cumulative FAN of 5.07 mgFAN/kgVSadded was evolved, which was lower than that in T1 but similar to the situation in T2. The lowest FAN was observed in T3, indicating that a moderate frequency of dilution might be conducive to alleviate free ammonia inhibition. Graphical abstract: Image 1 Highlights: The release of ammonia nitrogen was related to the solid content of the feedstock. Lower dilution frequency reduced the proportion of FAN in ammonia nitrogen balance. Higher dilution frequency promoted the conversion of nitrogenous compound to N2 . Low frequency dilution might be one choice for alleviating ammonia inhibition.